CORPORATE PRACTICES FOR COMPANIES RISK CAPITAL - Ugarte Silva, Saturnino Alfonso (2009)
The compliance and governance practices is not a new challenge for venture capital entities, it is rather the day day since the crisis of investor confidence has resulted in radical changes. More than ever it is vital that financial institutions consider their implementation from a global perspective. The theme is focused on identifying major transactions taking place in the process of identifying business risks and critical control activities designed to cover control objectives of financial reporting.